Implementasi Nilai-Nilai Pancasila Melalui Organisasi Intra Sekolah Osis di Sekolah Menengah Pertama SMP Negeri 3 Una-Una - Andina; Asmun W. Wantu; Zulfikar Adjie (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2026)
This study aims to describe the implementation of Pancasila values through the Student Council Organization (OSIS) at SMP Negeri 3 Una-Una and to identify the obstacles encountered in carrying out the role of OSIS as a medium for fostering and internalizing Pancasila values. This research employs a qualitative approach with a descriptive research design. The study was conducted at SMP Negeri 3 Una-Una, Tojo Una-Una Regency, Central Sulawesi Province. The data sources consist of primary data obtained through interviews and observations, as well as secondary data derived from school documents and OSIS activity archives. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis was carried out through the stages of data reduction, data display, and inductive conclusion drawing. The results of the study indicate that OSIS plays a strategic role in implementing Pancasila values through religious activities, nationalistic activities, deliberation, community service, and character-strengthening programs that emphasize habituation and practical application. Pancasila values have been internalized in students’ behavior, although their conceptual understanding remains limited. The obstacles encountered include limited student resources, low participation of some OSIS members, inadequate facilities and infrastructure, minimal support from the family environment, and limited mentoring time. The conclusion of this study shows that the implementation of Pancasila values through OSIS has been carried out fairly well; however, it still requires strengthened guidance, mentoring, and continuous support to ensure optimal internalization of values.